Short-course Rapamycin Treatment Preserves Airway Epithelium and Protects Against Bronchiolitis Obliterans - Gillen, Jacob R. (2013)
BACKGROUND: Damage to airway epithelium is closely related to the development of bronchiolitis obliterans (BO) in pulmonary transplantation. Rapamycin protects against BO development in a murine model, but its use in lung transplant patients is limited by its side effects. We hypothesized that short-course rapamycin dosing could be used to prevent airway epithelium loss and protect against BO development in a murine model. METHODS: A total alloantigenic mismatch, murine, heterotopic tracheal transplant model of BO was used. Animals were treated with either rapamycin or dimethyl sulfoxide (controls) according to 1 of 3 treatment regimens: 1) day 1 through 14 post-transplant, 2) day 3 through 7 post-transplant, or 3) day 14 through 28 post-transplant. Epithelial loss was assessed via H&E stains at 14 and 28 days post-transplant. Tracheal luminal obliteration was assessed at 28 days. RESULTS: Early rapamycin treatment was protective against epithelial loss at 14 days post-transplant compared to controls (p<0.001). Rapamycin treatment from days 1-14 was more effective at epithelial preservation (p=0.002) and reducing luminal obliteration (p<0.001) at 28 days compared to rapamycin treatment from days 3-7. Late rapamycin treatment (days 14-28) allowed for recovery of the previously denuded epithelium at 28 days (92.5% epithelial loss to 35.6%) and a reduction in BO (p<0.001). CONCLUSIONS: Short-course rapamycin treatment protects against airway epithelium loss and subsequent development of bronchiolitis obliterans in a murine model. Because of its immunosuppressive and anti-fibrotic effects, rapamycin may prove to be the ideal medication to prevent chronic rejection and BO in lung transplant patients.